Pendidikan Karakter Nasionalisme tema Integrasi Nasional dalam Bingkai Bhinneka Tunggal Ika pada Siswa Kelas X SMA Negeri 6 Yogykarta - Ahadi, Taufik Irfan; Kusumawati, Intan; Kurnia, Heri (Academy of Social Science and Global Citizenship Journal, 2023)
The study was conducted to examine the character education of nationalism with the theme of national integration in the framework of Bhinneka Tunggal Ika in the X grade students of SMA Negeri 6 Yogyakarta. This study aims to find out, (1) the process of character education of nationalism with the theme of national integration in the Bhinneka Tunggal Ika frame in class X students at SMA Negeri 6 Yogyakarta, (2) the results of nationalism character education on the theme of national integration in the Bhinneka Tunggal Ika frame in class X students at SMA Negeri 6 Yogyakarta. This research uses descriptive qualitative research. The research instruments used ware observation, interviews and documentation. The data obtained ware collected through observation, interviews and documentation. Data analysis techniques in the study are data reduction, data presentation, and drawing conclusions. The results of this study are as follows: (1) The process of nationalism character education with the theme of national integration in class X students of SMA Negeri 6 Yogyakarta is carried out by integrating it into Pancasila and Citizenship Education Class X subjects, beside being integrated into character education learning, it is also implemented through cultural habits school. In the Pancasila and Citizenship education lesson it self, nationalism character education with the theme of national intgeration is taught using contextual tekstual student center methods or such as using problem solving methods. So that students are required to be able to solve existing social problems about the character of nationalism and national integration and provide solutions to these problems. (2) The results of nationalism character education with the theme of national integration in class X students of SMA Negeri 6 Yogyakarta can be seen from the cognitif values and affective values of students. The affective value can be seen from the participation of students in activities organized by the school such as flag ceremonies, paskibraka selection, and scout extracurricular activities which have increased and become indicators of achieving the character of nationalism.